European Airlines Conduct after September 11th - Marco Alderighi; Alessandro Cento (European Regional Science Association (ERSA), 2003)
This paper analyses the network reorganisation that European carriers have implemented after September 11th in the transatlantic flights. We model carriers' conduct as a mixture of short- and long-term goals where the weights depend on firm-specific variables (adjustment costs, financial situation) and subjective expectations on the crisis duration. Data provide some support to our conjectures that high adjustment costs, induce low reaction to the demand fall and that a bad financial situation shifts the carries attention to short-term profitability. Finally, the analysis of the composition of short- and long-term reaction provides some insights into the carriers' perspectives of the crisis duration.
Keywords: 330